Exopolysaccharide from the mice ovarian bacterium Bacillus velezensis OM03 triggers caspase-3-dependent apoptosis in ovarian cancer cells - Sreejesh Pilakkavil Chirakkara, Asha Abraham (Journal of Applied Pharmaceutical Science, 2023)
Exopolysaccharides (EPS) were isolated from mice ovarian microflora Bacillus velezensis OM03 to investigate their chemical properties and cytotoxic potential against human ovarian carcinoma cell lines PA-1 and SKOV-3. The structural analysis of EPS from OM03 using Fourier Transform Infra-Red spectroscopy, X-ray diffraction, Scanning Electron Microscopy, and Gas chromatography-Mass revealed that it is a novel heteropolysaccharide made of glucose and mannose units connected with α-1,4 and β-1,4 bonds. Attractively, the EPS inhibited the proliferation of SKOV-3 and PA-1 cancer cells in a concentration-dependent manner, with IC50 values of 620 and 238 μg/ml, respectively, according to 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide tests. Moreover, EPS-OM03 caused DNA fragmentation in PA-1 cell lines and boosted the expression of active caspase-3, both of which triggered apoptosis. Furthermore, the experiment with the chick embryo chorioallantoic membrane demonstrated that treatment with EPS-OM03 exhibits an in vivo antiangiogenic effect with an IC50 of 146 μg/ml. In conclusion, our work offers scientific support for the development and use of pharmaceuticals derived from the microbiome, and it suggests that the EPS from B. velezensis OM03 may be a lead molecule in the treatment of ovarian cancer.